2015
DOI: 10.1002/pc.23457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clay modification on the structure and properties of sulfonated poly(ether ether ketone)/clay nanocomposites

Abstract: Sulfonated poly(ether ether ketone) (SPEEK)/clay hybrid membranes were prepared using three types of commercially available clays, the sodium montmorillonite (IC), hydrophobic organo‐clay with long alkyl chains (OC), and organo‐clay with carboxylic acid end groups (HC). It was found that the SPEEK/HC hybrid membranes achieved the best clay dispersion, with the exfoliation of the clay nano‐platelets when the filler loading was < 10 wt%. The incorporation of the carboxylic acid groups in clay layers also improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…The SPEEK/S15 membrane has the lowest water uptake capacity at 2.6% and the lowest swelling ratio at 1.8% due to the lower water content. He et al synthesized organo‐clay‐added SPEEK nanocomposite membranes and used sodium montmorillonite, organo‐clay with alkyl group as fillers. The authors reported that the water uptake of the organo‐clay‐added SPEEK membranes decreased when the amount of clay addition was increased.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SPEEK/S15 membrane has the lowest water uptake capacity at 2.6% and the lowest swelling ratio at 1.8% due to the lower water content. He et al synthesized organo‐clay‐added SPEEK nanocomposite membranes and used sodium montmorillonite, organo‐clay with alkyl group as fillers. The authors reported that the water uptake of the organo‐clay‐added SPEEK membranes decreased when the amount of clay addition was increased.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SPEEK polymer has greater interface and separation than Nafion due to its settled sulphonic acid group . Due to the advantages of combining both polymeric and inorganic properties, inorganic‐organic composite membranes are relatively more promising than modifying the Nafion membranes . Also, modifying a suitable membrane such as SPEEK instead of improving the poor properties of Nafion is more cost effective and feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of an organic material's properties (conductivity, flexibility, processability) and an inorganic material's properties (chemical and thermal stability, decreased fuel permeability, increased water retention) led to improved results. Various materials that have been used extensively for composite membrane fabrication include MO 2 inorganic oxides (M = Ti, Zr, Si), clays, zeolites, and heteropoly acids . Heteropoly acids (HPAs) are one of the good inorganic modifiers because of their unique properties like high conductivity, thermal stability, high selectivity, and noncorrosive nature (with a few exceptions) .…”
Section: Introductionmentioning
confidence: 99%
“…Power density of the sulfonated nanohybrid membrane exhibited significantly higher value of 33 mW cm -2 , against the value of 11 mW cm -2 measured for standard Nafion ® at similar current density. He et al (2015) investigated the effects of three types of clays; i.e., sodium montmorillonite (IC), hydrophobic organo-clay with long alkyl chains (OC), and organo-clay with carboxylic acid end groups (HC), on the structure and properties of SPEEK/clay nanocomposites. They found that the SPEEK/HC hybrid membranes achieved the best clay dispersion, higher proton conductivity (due to the interaction between the carboxylic acid groups in HC and sulfonic acid groups in SPEEK) and selectivity at low filler loading (<10 wt.%).…”
Section: Nanocomposite Pems With Layered Silicate Materialsmentioning
confidence: 99%